2007
DOI: 10.1074/jbc.m608204200
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin-1 Interactions with Fibulins Depend on the First Hybrid Domain and Provide an Adaptor Function to Tropoelastin

Abstract: Fibrillin-containing microfibrils in elastic and nonelastic extracellular matrices play important structural and functional roles in various tissues, including blood vessels, lung, skin, and bone. Microfibrils are supramolecular aggregates of several protein and nonprotein components. Recently, a large region in the N-terminal portion of fibrillin-1 was characterized as a multifunctional protein interaction site, including binding sites for fibulin-2 and -5 among others. Using a panel of recombinant fibrillin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
112
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 66 publications
1
112
1
1
Order By: Relevance
“…While fibulin-2 and -4 are present at the interface between the central elastin core and its surrounding fibrillin microfibrils (8,18), fibulin-1 is located within the elastin core and fibulin-5 is associated with fibrillin microfibrils (8,19). Consistent with these observations, in vitro protein binding studies have shown that all fibulins are capable of binding to tropoelastin, albeit with different affinities (8,20,27), and that fibulin-2, -4, and -5 interact with the N-terminal region of fibrillin-1 (5,6,18).…”
mentioning
confidence: 74%
“…While fibulin-2 and -4 are present at the interface between the central elastin core and its surrounding fibrillin microfibrils (8,18), fibulin-1 is located within the elastin core and fibulin-5 is associated with fibrillin microfibrils (8,19). Consistent with these observations, in vitro protein binding studies have shown that all fibulins are capable of binding to tropoelastin, albeit with different affinities (8,20,27), and that fibulin-2, -4, and -5 interact with the N-terminal region of fibrillin-1 (5,6,18).…”
mentioning
confidence: 74%
“…Unlike fibulin-1, fibulin-2 binds directly to fibrillin-1 and has been shown to localize to the interface between the amorphous elastin core and microfibrils in skin . Fibulin-3 does not bind to fibrillin-1 (El-Hallous et al, 2007) and has been shown to only weakly interact with tropoelastin (Kobayashi et al, 2007). Fibulin-3 is expressed in capillaries, but not large blood vessels (Giltay et al, 1999) and most likely does not have a role in elas-tic fiber assembly.…”
Section: Fibulinsmentioning
confidence: 99%
“…Fibulin-3 is expressed in capillaries, but not large blood vessels (Giltay et al, 1999) and most likely does not have a role in elas-tic fiber assembly. Fibulin-4 binds fibrillin-1 (El-Hallous et al, 2007) and shows moderate affinity for tropoelastin. Fibulin-4 has been localized to microfibrils (Kobayashi et al, 2007).…”
Section: Fibulinsmentioning
confidence: 99%
See 1 more Smart Citation
“…After subcloning the 1416-base pair PCR product in the pCRII-TOPO vector (Invitrogen, Carlsbad, CA), an 874-base pair SphI ϫ NotI fragment from the resulting plasmid was ligated with the 5677-base pair SphI ϫ NotI fragment from pBS-rFBN3C-1, resulting in pBS-rFBN3-C. This plasmid was digested with NotI ϫ NheI, and the 4127-base pair fragment was ligated with the vector backbone of the pDNSP-rF1F plasmid (El-Hallous et al, 2007). The final expression plasmid pDNSP-rFBN3-C encodes the BM40 signal peptide for secretion, generating an artificial APLA sequence, followed by the human fibrillin-3 amino acid sequence and a heptahistidine tag (APLAD 1321 -R 2684 HHHHHHH).…”
mentioning
confidence: 99%